2010
DOI: 10.1109/tgrs.2009.2027896
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Calibration of ASCAT Using CMOD5.n

Abstract: The Advanced Scatterometer (ASCAT) onboard the Metop-A satellite became operational shortly after launch in 2006, and an absolute calibration using three transponders was achieved in November 2008. In this paper, we describe how the CMOD5.n ocean backscatter geophysical model function (GMF), which was derived using data from previous scatterometers onboard the European Remote Sensing 1 and 2 satellites (ERS-1 and ERS-2), was used to derive backscatter bias correction factors. The purpose is to remove the bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 13 publications
2
54
0
Order By: Relevance
“…Here we use Level 2b ASCAT near realtime data (version 1.10) distributed by EUMETSAT and by KNMI at 25 Â 25 km 2 resolution. Comparisons to independent mooring and shipboard observations by Bentamy et al [2008] and Verspeek et al [2010] show that ASCAT wind speed and direction has accuracies similar to QuikSCAT.…”
Section: Datamentioning
confidence: 83%
See 2 more Smart Citations
“…Here we use Level 2b ASCAT near realtime data (version 1.10) distributed by EUMETSAT and by KNMI at 25 Â 25 km 2 resolution. Comparisons to independent mooring and shipboard observations by Bentamy et al [2008] and Verspeek et al [2010] show that ASCAT wind speed and direction has accuracies similar to QuikSCAT.…”
Section: Datamentioning
confidence: 83%
“…This implies that DW averaged over the whole range of azimuth and wind speed does not depend on the ASCAT incidence angle. Indeed, previous studies [e.g., Bentamy et al, 2008;Verspeek et al, 2010] have indicated that ASCAT wind speed distributions are not incidence angle dependent. Although it does not verify that the dependence of DW on q can be ignored at any specific W AS and 8, we assume that incidence angle may be eliminated from fitting parameters of the correction function dW.…”
Section: Effect Of Geophysical Model Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERA-interim wind also has lower resolution than the wind speed retrievals from ASAR. Supposing correctness in the ERA-interim wind fields (commonly used as a reference for validation [32,33]), the mismatch between its resolution (0.75° in latitude and longitude) and the SAR wind cells present a source of error for wind directions with variations in scales smaller than the ERA-interim resolution. Nevertheless, although with low temporal resolution, the results achieved with the available ASAR data had a finer spatial delimitation and higher levels of significance than the corresponding results with ERA-interim wind speeds.…”
Section: Figure 12mentioning
confidence: 99%
“…AMI sensor onboard ERS-1 and ERS-2 satellites and the Advanced SCATterometer (ASCAT) onboard the MetOp-A satellite (Figa-Saldaña et al, 2002), were designed to provide retrievals of real (stability-dependent) winds (Offiler, 1994;Hersbach et al, 2007). However, the CMOD5.n GMF was developed more recently to provide equivalent neutral winds (Hersbach, 2010;Verspeek et al, 2010) and is now used to produce the operational ASCAT level 2 wind products at the Royal Netherlands Meteorological Institute (KNMI). The information on low-level atmospheric circulations provided by scatterometers can be used to improve numerical weather forecasts.…”
Section: Introductionmentioning
confidence: 99%